Pengelolaan Keuangan Daerah dan Good Governance terhadap Kinerja Satuan Kerja Perangkat Daerah - Mbipi, Saverius Dhuri; Assih, Prihat; Sumtaky, Maxion (AFRE (Accounting and Financial Review), 2021)
This study aims to describe regional financial management which includes: planning and budgeting, implementation and administration and accountability of regional finances; and transparency which includes transparency and accessibility; as well as the accounta-bility of regional financial reporting, the effectiveness of internal and external party super-vision, and the performance of Regional Work Units; analyze the effect of the effectiveness of financial planning, the effectiveness of budget execution control, transparency and ac-countability of financial reporting on the performance of Local Government Work Units. This type of research is explanative. The number of samples in this study were 32 respond-ents. The data collection technique used a questionnaire. The analysis technique uses de-scriptive analysis and multiple linear regression analysis. Regional financial management which includes; the effectiveness of financial planning, the budget formulation process, the characteristics of the clarity of budget targets and control have an effect on the performance of regional work units. Meanwhile, transparency and accessibility of regional financial reporting and accountability of regional financial reporting have no effect on the perfor-mance of regional work units. Â DOI: https://doi.org/10.26905/afr.v3i2.5503